Making the Global Studio sustainable: project update - Erik Bohemia; Kerry Harman (2009)
Over the past three years the School of Design at Northumbria University has been experimenting with an innovative learning and teaching model named the Global Studio. The Global Studio is a teaching, learning and research initiative that links design students, academics and industry partners across the globe. For example, in one project last year staff and students from Northumbria University collaborated across distance with students from Hong-ik University in Korea and industry partners from Motorola based in London and Seoul. In another project, Northumbria students collaborated with students from Auburn University in the US and their industry partners, Great Southern Wood. This year Northumbria students are collaborating on design projects with students from Ohio State University in the US, RMIT in Australia, Hong-ik in Korea, Napier in Scotland and a multinational organisation from the Healthcare industry.